Ultrasonic Assisted Synthesis and Characterization of Chitosan Graf with 2-(Dimethylaminoethylmethacrylate) (Dmaema) Cs-G-Pdmaema - Dalhatu, Sani Nazifi; Modu, Kolo Alhaji; Mahmoud, Auwal Adamu; Adamu, Harami M.; Murtala, Ridwanu (Journal of Physical Sciences, 2021)
Purpose: Many researchers reported the use of chitosan in various applications due to its desirable properties, but then its application in a certain condition is limited due to its lower mechanical stability, lower solubility in certain solvents, and crystallinity of the polymer. Numerous report has been published by many researchers across the world modifying chitosan to enhanced its properties thereby improving its application in various field Methodology: Poly (2-dimethylaminoethyl methacrylate) (Cs-g-PDMAEMA) were successfully synthesized by Ultrasonic methods for the first time. The synthetic method was optimized by varying various reaction parameters and reaction conditions. The grafting was confirmed by characterizing the copolymer with FTIR, XRD, XPS, SEM, TGA, DTG, and DTA. Findings: The results show a good percent grafting and percent yield up to 132%G and 94.7%Y at optimum condition, and also shows a decrease of thermal stability and crystallinity of chitosan, there was improved in porosity of the surface, and complexity of the surface functional group making it a good candidate for metal chelating. Observing various changes in the spectrum of these derivatives and that of pure chitosan in addition to the change in properties of these polymers such as surface morphology, thermal stability, and crystallinity. Uniqe Contribution to Theory, Practice and Policy: It was suggested that this modification may improve the application of these polymers.